2009
DOI: 10.1158/0008-5472.can-09-0493
|View full text |Cite
|
Sign up to set email alerts
|

Nitrosative Stress–Induced S-Glutathionylation of Protein Disulfide Isomerase Leads to Activation of the Unfolded Protein Response

Abstract: The rapid proliferation of cancer cells mandates a high protein turnover. The endoplasmic reticulum (ER) is intimately involved in protein processing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
134
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(137 citation statements)
references
References 39 publications
1
134
1
1
Order By: Relevance
“…associate with various pathologies, such as diabetes, atherosclerosis, inflammatory, and cancer [11,[14][15][16]. In the present study, serum S-glutathionylated proteins were significantly increased in patients with CS, suggesting an imbalance of the redox state and protein thiols in the serum.…”
Section: Altered Levels Of S-glutathionylated Proteins Have Been Recementioning
confidence: 50%
See 1 more Smart Citation
“…associate with various pathologies, such as diabetes, atherosclerosis, inflammatory, and cancer [11,[14][15][16]. In the present study, serum S-glutathionylated proteins were significantly increased in patients with CS, suggesting an imbalance of the redox state and protein thiols in the serum.…”
Section: Altered Levels Of S-glutathionylated Proteins Have Been Recementioning
confidence: 50%
“…Recent studies have demonstrated that S-glutathionylation can produce discrete modulatory effects on protein function [12,13]. Therefore, S-glutathionylated proteins have been actively investigated with reference to problems of biological interest and as potential biomarkers of human diseases associated with oxidative stress [11,[14][15][16]. Nakamoto M,et al page 4 In this study, we developed an antibody to specifically recognize the S-glutathionylated proteins, and then we investigated whether the serum S-glutathionylated proteins increased in patients with different stages of CS.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the application of peroxynitrite (ONOO -) or Snitrosoglutathione (GSNO, 10-500 lM) to induce S-glutathionylation is also found in the literature (12,38,125,129). The application of peroxynitrite is of high physiological relevance but as peroxynitrite can also induce other modification including S-nitrosylation, additional experiments should be performed to further dissect the exact modification mechanism.…”
Section: Induction Of S-glutathionylationmentioning
confidence: 99%
“…After that, the cells are lysed and streptavidinconjugated agarose beads (or magnetic beads) are used to pull down the BioGEE-conjugated protein complex, and the protein of interest is detected by the protein-specific antibodies (145). Alternatively, the BioGEE-protein complex could be immunoprecipitated (IP) first with specific antibodies against the protein of interest and then immunoblotted (IB) with streptavidin or anti-biotin antibody (125). A variation of this experiment is to avoid using BioGEE.…”
Section: Biochemical Testsmentioning
confidence: 99%
“…Other substrates for PDI that also have their intermediates identified are lysozyme (4 disulfides) (van den and 2 modified RNases, RNaseT1 (2 disulfides) and glutathionylated RNAseT1, (Ruoppolo and Freedman, 1995;Ruoppolo et al, 1996). Reduced RNaseT1 behaves in the assay as reduced RNase, while the glutathionylated substrate has to be deglutathionylated in the first step, which may also be mediated by PDI Townsend et al, 2009). Transposition of oxidative refolding assays to biological samples relies on the same difficulties as those of isomerase activity discussed previously.…”
Section: An Overview Of Pdi Activity Assaysmentioning
confidence: 99%